TINJAUAN SISTEM KERJA SAMA (MUKHABARAH) DI BIDANG PERTANIAN DALAM PERSPEKTIF ISLAM - Muspita sari (AL-KHARAJ, 2022)
AbstractThis article aims to explain about cooperation in the management of agricultural land in accordance with Islamic law, whether it is allowed or not allowed in Islam. This cooperation is known as mukhabarah. This kind of cooperation system is still a matter of debate in the Islamic world, especially among fiqh scholars. This is based on the presence or absence of elements of usury, maysir, gharar, and others in its process. Thus, it is able to provide an overview of how the cooperative mechanism for managing agricultural land is recommended in Islam in order to provide benefits for all stakeholders because it can be a medium for helping people who do not own land but are able to cultivate. It also makes it easier for land owners to keep their land productive and earn income. ABSTRAK Artikel ini bertujuan untuk menjelaskan mengenai kerja sama dalam pengelolaanilahan pertanian yang sesuai dengan syariat Islam apakah diperbolehkan atau tidak dibenarkan dalam islam. Kerja sama ini disebut dengan istilah mukhabarah. Sistem kerja sama semacam ini masih menjadi perdebatan dalam dunia Islam khususnya dikalangan ulama fikih. Hal tersebut disandarkan pada ada atau tidak adanya unsur riba, maysir, gharar, dan lain-lain dalam proses kerja sama tersebut. Sehingga mampu menggambarkan bagaimana mekanisme kerja sama pengelolaan lahan pertanian yang dianjurkan dalam Islam agar memberikan maslahat bagi semua pihak yang bersangkutan, karena dapat menjadi wadah tolong menolong antara masyarakat yang tidak memiliki lahan tapi mempunyai kemampuan untuk menggarap serta memudahkan bagi pemilik lahan agar lahannya tetap produktif serta dapat berpenghasilan.